(untitled) (Third Sector Social Economic Review, 2023)
The Enron accounting scandal in 2000, economic (2008-Mortage Crisis) and pandemic (Covid-19) crises, and the development of technology have increased the interest in fraud and cheating. In this study, academic studies on ""cheating"" in Turkey were examined by content analysis method using EBSCO and YÖK Thesis databases. An important part of the studies accessed from the databases are aimed at increasing the level of knowledge and awareness about fraud and forensic accounting with theoretical and conceptual explanations. Studies containing questionnaires were on the perception and tendency of cheating, detection and prevention of cheating in different sample groups. In studies that use information technologies (artificial intelligence/data mining/algorithm) as a new and proactive approach, the focus is on detecting and preventing fraud. The difficulty of accessing financial data due to reasons such as trade secrets, protection of personal data, continuation of the judicial process, loss of reputation, although the studies conducted over the years tend to increase, constitute the limitations of the studies on fraud. The fact that different financial instruments (such as crypto money) and applications enable decentralized transactions, especially with the developing information technologies, makes it more difficult to detect, prevent and compensate for the damages. Developing new methods as well as detection and prevention methods with proactive approaches and artificial intelligence may be beneficial in preventing fraud. It will also be useful to develop applications such as a whistleblowing line and rewards to detect fraud, to redefine and activate the audit function. However, the important thing is to eliminate the causes of fraud. This will only happen with an educated and moral society.